The Sumatra-Andaman Tsunami in Banda Aceh: A Linear Model for Representation - Jorge Corrêa de Araújo; Rosa García Márquez (REMAT, 2023)
The Sumatra-Andaman earthquake that occurred on December 26, 2004 was the second largest earthquake in the past 40 years, with a moment magnitude of 9.1 - 9.3. The rupture took place at a depth of 1.3 km along a large boundary fault between the Indian and Burma plates. The fault slip reached up to 20 meters near Banda Aceh, Sumatra Island, and was more rapid compared to the northern end between the Indian Plate and the Andaman archipelago, where landslide took almost one hour to reach from 7 to 20 meters. Based on this data and other observations, it was possible to estimate that the main tsunami originated approximately 390 km from Banda Aceh city. Although the energy transmitted by the simple harmonic waves adopted in this study was shorter than that reported by other references, it was still significant. The estimated arrival time for the tsunami in Banda Aceh using a simple model was reasonably consistent with the actual observation time. This agreement suggests that the origin region of the estimated in this study is likely within the most probable starting point of the tsunami. The wave amplitude near the coast, as estimated by the model, fell within the observed range reported by the references. The methodology developed in this study seems to be suitable for obtaining initial estimates of several important parameters involved in events of this nature.